Association between social inclusion and mental health among people with disabilities engaged in sports clubs: a cross-sectional survey - Al Harthy, Sobhi Saeed; Hammad, Mohammad Ahmed; Awed, Huda Shaaban (Frontiers in Psychology, 2025)
ObjectiveParticipation in sports is known to promote social inclusion and mental health. However, barriers that limit the participation of people with disabilities in sports potentially exclude them from enjoying the social and mental health benefits. This study aimed to assess the level of social inclusion experienced by people with disabilities participating in sports clubs in Saudi Arabia, and to examine its relationship to specific mental health outcomes, namely, overall mental health, depression, and anxiety.MethodsIn this cross-sectional survey, people with disabilities were recruited from sports clubs in southern Saudi Arabia. Club presidents were contacted via email or social media messaging services to access their member lists and identify potential participants. The sample comprised 205 participants who met the inclusion criteria and provided informed consent (age 18–40 years, mean = 29.8 years, standard deviation = 3.82 years). Participants received an email with a link to a Google Form containing information about the study and the questionnaire, which included the Social Inclusion Questionnaire for People with Disabilities, Mental Health Continuum - Short Form, Centre for Epidemiological Studies Depression Scale-10, and Generalized Anxiety Disorder-7. Data were analyzed using SPSS version 20. Cronbach’s alpha was used to assess the reliability of the study instruments. In addition to descriptive statistics, bivariate analyses (t-tests or one-way analysis of variance, as appropriate) were conducted to assess group differences. Pearson’s correlation coefficient and hierarchical regression analysis were used to examine the association between social inclusion and mental health outcomes (controlling for age, gender, and type of disability in regression analysis).ResultsSlightly over half of the participants (53.65%) reported moderate to high social inclusion scores, while 46.34% had low inclusion scores. Social inclusion was positively correlated with overall mental health it was identified a significant predictor of mental health in the present sample.ConclusionPresent findings suggest that, among people with disabilities who are engaged in sports clubs, social inclusion was associated with better overall mental health and lower incidence of anxiety and depression. These results suggest the potential for sports clubs to become facilities that prevent the exclusion of people with disabilities and to support their physical, mental, and social well-being.